If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -4(x + 3) = 5 Reorder the terms: 5 + -4(3 + x) = 5 5 + (3 * -4 + x * -4) = 5 5 + (-12 + -4x) = 5 Combine like terms: 5 + -12 = -7 -7 + -4x = 5 Solving -7 + -4x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -4x = 5 + 7 Combine like terms: -7 + 7 = 0 0 + -4x = 5 + 7 -4x = 5 + 7 Combine like terms: 5 + 7 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| 3-y=2x | | (y^2-7x)(y-5)= | | 2y-6y-10=-2 | | 3x=-2y+10 | | r^2+8r+7=0 | | 3x+2x+7=41 | | 3x^2+7x-6=0 | | 2d-10=6(7-4d) | | 7x+2y=-8 | | 2x=y+16 | | 2(b+2)-(6+b)=-3 | | (x-6)(x+3)= | | -y=0 | | (3a+5)(3a-4)= | | m-9.45=2.7 | | 0=-5y-7x-15 | | -6(-8a-2b+3)= | | 6x+24=8x+16 | | -16x-8=-2y | | 12y-7=19-y | | -3(7+3b)=-6b-3 | | 8d+13=21d | | 3x+5y-11=0 | | 3(3+3x)-2=52 | | 8z^2+32z-az-4a=0 | | -15x^2-115x-150=0 | | (3a-5)(3a+4)= | | 6x+26=2x+144 | | 0=10y-2x+40 | | w^2=27-6w | | 7c+5=6+7c | | 4(2x-2)=8 |